Cognitive Behavioral Therapy and its Effect on Self-Efficacy among Adolescent Bullying Victims (12–16 Years Old) at MTs Darul Azhar - Dewy, Tika Sari; Maulidah, Noor (Journal of Health and Nutrition Research, 2025)
Bullying constitutes a detrimental experience for victims, frequently leading to diminished self-efficacy. Group Counseling incorporating Cognitive Behavioral Therapy (CBT) has emerged as a potential therapeutic intervention to enhance self-efficacy in individuals affected by bullying. This study aimed to investigate the effect of Group Counseling utilizing Cognitive Behavioral Therapy on the improvement of self-efficacy among victims of bullying. A pre-experimental, one-group pretest-posttest design was employed. The study sample consisted of 20 participants identified as bullying victims who exhibited low initial levels of self-efficacy. Measurement instruments included the Adolescent Peer Relations Instrument (APRI) bullying questionnaire and a validated Self-Efficacy Questionnaire, administered before and after the intervention. Participants underwent Group Counseling sessions based on CBT principles. Pre-intervention assessment revealed that all 20 participants (100%) reported low levels of self-efficacy. Following the completion of the Group CBT intervention, a significant shift was observed, with 18 participants (90%) demonstrating moderate levels of self-efficacy. A paired t-test analysis confirmed a statistically significant increase in self-efficacy scores post-intervention (p < 0.001). The findings indicate that Group Counseling integrated with Cognitive Behavioral Therapy significantly enhances self-efficacy among individuals who have experienced bullying